2022
DOI: 10.3390/medicina58080982
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Core Stability and Upper-Extremity Performance in Male Collegiate Athletes

Abstract: Background: The purpose of this study was to investigate the correlation of core stability, as measured by the McGill and double-leg lowering (DLL) test, with upper-extremity performance, as measured by the upper-quarter Y-balance test (UQYBT), medicine ball throw test (MBTT) and functional throwing performance index (FTPI) test, in collegiate athletes. Materials and Methods: A sample of 61 collegiate athletes from Imam Abdulrahman Bin Faisal University participated in the study. Their core stability was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…Again, our hypothesis can just partly be confirmed as only the CS of the throwing and the non-throwing arm reach and the IL reach of the non-throwing arm reach were significantly improved in favour of the INT group. This finding goes in line with possible correlations between shoulder mobility/stability and core strength in different populations ( 35 , 44 ). As in our study partially improvements were detected for the parameters of muscular strength, positive adaptations in terms of shoulder mobility/stability as secondary effects of core strengthening training were also unlikely.…”
Section: Discussionsupporting
confidence: 89%
“…Again, our hypothesis can just partly be confirmed as only the CS of the throwing and the non-throwing arm reach and the IL reach of the non-throwing arm reach were significantly improved in favour of the INT group. This finding goes in line with possible correlations between shoulder mobility/stability and core strength in different populations ( 35 , 44 ). As in our study partially improvements were detected for the parameters of muscular strength, positive adaptations in terms of shoulder mobility/stability as secondary effects of core strengthening training were also unlikely.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that higher core muscle strength endurance is associated with higher shoulder mobility/stability goes in line with Westrick et al ( 18 ) who reported significant positive relationships of YBT-UQ performance with dominant ( r = 0.38, p = 0.04) and non-dominant ( r = 0.45, p = 0.01) side lateral trunk endurance. In accordance, Nuhmani et al ( 22 ) found significant positive correlations between the McGill Score and the YBT-UQ ( r = 0.46, p = 0.01) as well as the MBTT ( r = 0.67, p = 0.02). The present associations may be explained by the fact that the Bourban test is an all-out test that is performed until continuation is no longer possible therefore requiring good level of strength endurance which is also needed during the YBT-UQ.…”
Section: Discussionsupporting
confidence: 72%
“…Based on the findings of other studies ( 18 , 22 ) that reported correlations between core strength and performance parameters we hypothesized that correlations existed between core strength and (a) the performance parameter (YBT-UQ) and (b) the sport-specific parameter (throwing velocity) in handball players.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations